A Sense of (Non)Place: Rethinking the ‘Generic City’ in terms of the Habit-body - Budhyarto, Mitha (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2011)
A ‘nonplace’, in Marc Augé’s view, may be defined in contrast to what he refers to as ‘anthropological place’. It is a space which cannot be defined as relational, or historical or concerned with identity. This article explores the sense of (non)place by answering these questions: if it is true that ‘who’ we are is defined by ‘where’ we are, insinuating that places do have an important role in shaping our identities, then what do these nonplaces tell us about us? In places that lack any defining features and reflects little of the unique local geography in which they are in, can we still develop a sense of place? What is needed now is a shift from the initial prioritising of ‘cultural contexts’, to the ‘context of the embodied’, emplaced, individual subject, a context that precedes any cognitive framework. Bearing in mind this shift in focus to the body, a phenomenological analysis of nonplaces then becomes necessary. The experiential value of a place must be assessed according to a lived, embodied engagement with it. Rem Koolhas’ view of a kind of ‘generic city’ in which urban dwellers now live has worldwide reverberations. This paper argues that a phenomenological analysis that puts emphasis on the subjective, embodied lived experience is a necessary step to make. By focusing on the body, the strict categorisations that have led to the negative connotations to nonplaces begin to lose their rigidity. Keywords:*Nonplace, *space, *identity, *geography, *a sense of place, *experience, *environment, *context of the embodied, *habit-body, *flesh of the world, *generic city, *interaction, *surrounding